The immunophilin ligand FK506, but not GPI-1046, protects against neuronal death and inhibits c-Jun expression in the substantia nigra pars compacta following transection of the rat medial forebrain bundle - Winter, Christine; Schenkel, Johannes; Bürger, Erich; Eickmeier, Carl Wilhelm; Zimmermann, Manfred; Herdegen, Thomas (Neuroscience, 1999)
The immunophilin ligand FK506 (Tacrolimus) is used for prevention of graft rejection following organ transplantation. FK506 is a high-affinity ligand for FK506-binding proteins, an immunophilin subgroup of peptidyl-prolyl-cis/trans-rotamases abundant in the mammalian brain. Here, we demonstrate that FK506 is a potent survival factor that prevents neuronal cell death following axotomy of central intrinsic neurons. Administration of FK506 (2mg/kg, s.c., per day for two days pre-axotomy and for up to eight days post-axotomy) effectively delayed and reduced the death of axotomized neurons in the substantia nigra pars compacta following transection of the medial forebrain bundle. In saline-treated controls, 75%, 89% and 92% of nigral neurons died after 25, 50 and 60days post-axotomy, respectively. In contrast, application of FK506 resulted in survival of 46%, 44% and 28% of the axotomized nigral neurons, and the majority of these surviving neurons showed continuous expression of tyrosine hydroxylase, the pacemaker enzyme for dopamine synthesis. Moreover, FK506 significantly reduced the expression of the inducible transcription factor c-Jun and its N-terminal phosphorylation and prevented the axotomy-induced suppression of the constitutive transcription factor ATF-2 in neurons of the substantia nigra and mammillary body. The latter is also axotomized by the coincident transection of the mammillothalamic tract, but the mammillary neurons survive the axotomy. In contradistinction to FK506, the non-immunosuppressive FK506-binding protein ligand GPI-1046 (25 or 12.5mg/kg, applied once or twice per day for two days pre-axotomy and for eight days post-axotomy) was completely ineffective for all these parameters investigated. Finally, FK506, but not GPI-1046, impressively accelerated the recovery from surgery. Our data provide the first evidence that FK506 acts as a neuroprotective molecule that rescues axotomized otherwise degenerating central intrinsic neurons in the adult mammalian brain by mechanisms that interfere with the transcriptional program of the axotomy-induced cell body response, such as activating transcription factor-2 suppression and c-Jun expression and phosphorylation.
Gesehen am 06.05.2021